Comparison of social support, depression and anger in diabetic and cardiac patients - Farwa Sadiq; Umm E Rubab Kazmi (Journal of the Pakistan Medical Association, 2021)
Objective: The present study explores the role of social support, depression and anger among diabetic and cardiac patients. Method: This cross sectional study comprised of 200 patients who were selected through purposive sampling strategy from outpatient departments (Cardiology and Endocrinology) of Government hospitals of Lahore (Jinnah Hospital and Services Hospital) and Muridke (Tehsil Headquarter Hospital) from April 2015- September 2015. Cardiac patients were 101(Men=51, Women=50) and diabetic type II patients were 99 (Men= 50, Women= 49). Siddiqui-Shah Depression scale (SSDS), Interpersonal Support Evaluation List (ISEL) and Trait Anger and Expression Scale (TAES) were administered on the patients. Result: The findings revealed that cardiac patients exhibit higher level of depression and receive more social support than diabetic patients. Furthermore, results reveal that low social support is a significant negative predictor of anger and depression among diabetic and cardiac patients. Conclusion: On the basis of findings, it is concluded that social support is a significant factor in the treatment of diabetes and cardiac diseases. This research is helpful for hospital administration in the counseling/management of such patients. Continuous...